Fractal and Fractional Analysis in Biomedical Sciences and Engineering - Andjelija Ž. Ilić (Fractal and Fractional, 2025)
The visual appearance of fractal patterns in biology has been noted from the early days of research in this field and, henceforth, has been studied for a long time [...]